Setting as a Marker of Space Time: Historical Mise en Scene in Hamka & Siti Raham Vol. 2 - Attabik Ahmad; Sri Wastiwi Setiawati (Institut Seni Indonesia Surakarta, 2026)
This article examines the role of year-transition settings as spatial and temporal markers in Hamka & Siti Raham Vol. 2. The study is prompted by the tendency of historical biopic scholarship to treat setting primarily as a supporting visual background, despite its significant contribution to create historical authenticity and narrative meaning. This study employed a qualitative approach by means of textual-contextual analysis to mise-en-scène elements, including architecture, set decoration, props, materials, color, lighting, and spatial organization. The data consist of scenes representing the historical periods of 1947, 1959, 1964, 1966, 1970, 1972, and 1975. The findings revealed that setting operates through three interrelated dimensions: locative, temporal, and symbolic functions. Its locative function was manifested through distinctive spatial environments that represent different stages of Hamka’s life, ranging from refugee shelters and family residences to detention cells, public religious platforms, mourning spaces, hospital rooms, and the Indonesian Ulema Council (MUI) National Congress Hall. The temporal function was constructed through period-specific visual elements, such as kerosene lamps, Jengki-style furniture, classic microphones, glass intravenous bottles, and state symbols. Meanwhile, the symbolic function emerged through the capacity of settings to reflect shifts in Hamka’s social position and life trajectory, from hardship and stability to imprisonment, recovery, reconciliation, loss, and eventual institutional recognition. The study also identified several instances of anachronism in textiles, materials, furniture, and typography. Nevertheless, these inconsistencies did not substantially diminish the setting ’s ability to construct a coherent spatial-temporal framework within the narrative. This article contributes to Indonesian biopic film studies by positioning setting as a primary analytical device for understanding the construction of temporality, spatiality, and historical reconstruction in cinematic representation.